The Use of Communication Methods in Traditional and Empirical Learning - Łukasik, Paweł (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2015)
Traditional and empirical learning are basic elements of the organisational learning process. Companies use different methods in the frame of traditional and organisational learning. The article presents communication methods functions in the use of organisational learning methods. The hypotheses have been proven by survey research done among more than two hundred respondents. At the end of the article I draw practical conclusions about the role of communication methods in organisational learning.